Obligation bond of Bernaldino San Pedro - San Pedro, Bernaldino
Bond signed by San Pedro, Francisco Pizzaro, and others.
Negative photocopy.
Collection material in Portuguese.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Pizarro, Francisco, -- approximately 1475-1541.; Bonds -- Portugal; Portugal -- Colonies -- America